Ohne Abschluss in die Bildungsgesellschaft - Solga, Heike
Education is and will probably remain the all-dominant topic of the 21st century. The consequences of a lack of or exclusion from education must be correspondingly dramatic. In the economic and sociological labour market literature, the same dominant explanatory pattern, the displacement mechanism, can now be found for the increasing disadvantage of low-skilled persons: the low-skilled are "displaced" by the better-skilled. In contrast to the theoretical considerations and empirical analyses in this book, the significance of processes of increasing discreditation, social impoverishment and stigmatization is worked out and emphasized - it is therefore more a matter of social inequality than of "displacement"
Keywords: Education; Identität; Jugend; Muslim; Migrationshintergrund; Lebenslauf; Deutschland; Arbeitsmarktforschung; Bildung; Labour market research; Social inequality; Soziale Ungleichheit; Electronic books